Selected issues for improving the composition of exhaust gases emitted by combustion engines by selecting the chemical structure of engine fuels - Kulczycki, Andrzej (Studia Ecologiae et Bioethicae, 2016)
The paper presents selected issues for improving the composition of exhaust gases emitted by combustion engines by selecting the chemical structure of engine fuels. It focuses on the most important for the air quality issues of NOx and PM emissions by road transport. The mechanism of combustion is determined and new theorie of energetic description of chemical reactions is introduced. This theory takes into account the influence of the chemical reactions environment on its course. It has been formulated thesis that the chemical structure of the fuel affect the distribution of energy in the volume of the combustion chamber of the piston engines and consequently the formation of environmentally harmful components of the exhaust gas. Based on this theory, selected results of research on the combustion of microemulsifying fuels and vegetable oil were verified by verifying the pre-formulated thesis.